The First Report of Multicentric Carpotarsal Osteolysis Syndrome Caused by MAFB Mutation in Asian - Pongsakorn Choochuen; Kitiwan Rojneuangnit; Thanitchet Khetkham; Sookkasem Khositseth (Case Reports in Medicine)
Multicentric carpotarsal osteolysis syndrome (MCTO) is a rare skeletal disorder characterized by aggressive osteolysis associated with progressive nephropathy. The early clinical presentation can mimic polyarticular juvenile idiopathic arthritis. Since 2012, MAFB mutations have been discovered in all MCTO patients. Therefore, the early diagnosis can be made based on genetic confirmation. We report the clinical manifestation of mineral bone disease and the molecular genetic study of a Thai female adolescent with MCTO. She presented with end-stage renal disease, bilateral wrist and ankle joint deformities, and subtle facial dysmorphic features. We identified a heterozygous missense MAFB mutation at nucleotide 197 from C to G (NM_005461.4; c.197C>G), predicting the change of amino acid at codon 66 from serine to cysteine (p.Ser66Cys), and the mutation was absent in the parents, indicating a de novo mutation. This report confirms the previous link between MAFB mutation and MCTO. Her unexplained hypercalcemia after a regular dose of calcium and active vitamin D supported an important role of MafB in the negative regulation of RANKL-mediated osteoclast differentiation. Therefore, we would encourage the physicians who take care of MCTO patients to closely monitor serum calcium level and perform a genetic study as a part of the management and investigation.